Educating Information Literacy for Electronic Resources in the Digital Age - Saiyed Yeop, Sarifah Fahimah (2011)
This article traces the development of the information literacy modules in engineering community in higher education environment. It examines the user’s education necessity of being information literate, and explores the research related to the concept. Included are reports on the research and findings from Subject Areas Relevancy Survey (SARS I and II) that has been conducted. Also examined are recent revisions in information literacy modules for subject matter standards that imply recognition of the process skills included in information literacy for electronic resources. The research outlines the impact of information literacy programs on the usage of electronic content for engineering students. It provides examples of information literacy in various contexts. The ‘live’ research is parallel with the implementation of subject guided or so called ‘taxonomy’ in searching process for electronic resources content.